2010
DOI: 10.1002/humu.21351
|View full text |Cite
|
Sign up to set email alerts
|

A rare novel deletion of the tyrosine hydroxylase gene in Parkinson disease

Abstract: Tyrosine hydroxylase (TH) enzyme is a rate limiting enzyme in dopamine biosynthesis. Missense mutation in both alleles of the TH gene is known to cause dopamine-related phenotypes, including dystonia and infantile Parkinsonism. However, it is not clear if single allele mutation in TH modifies the susceptibility to the adult form of Parkinson disease (PD). We reported a novel deletion of entire TH gene in an adult with PD. The deletion was first identified by copy number variation (CNV) analysis in a genome-wid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 13 publications
1
30
0
Order By: Relevance
“…Previously reported 4 large genomic deletions involving GJB6 [2527] were screened via quantitative PCR. CNV analysis for the genomic region of the GJB6 gene was performed with a TaqMan predesigned probe (Hs03843749, Chr13:20961484 on NCBI build 37) by using a previously described protocol [28]. For the Sanger sequencing, PCR reactions included 25 μg of genomic DNA with Taq DNA polymerase (Roche).…”
Section: Materials and Methodologymentioning
confidence: 99%
“…Previously reported 4 large genomic deletions involving GJB6 [2527] were screened via quantitative PCR. CNV analysis for the genomic region of the GJB6 gene was performed with a TaqMan predesigned probe (Hs03843749, Chr13:20961484 on NCBI build 37) by using a previously described protocol [28]. For the Sanger sequencing, PCR reactions included 25 μg of genomic DNA with Taq DNA polymerase (Roche).…”
Section: Materials and Methodologymentioning
confidence: 99%
“…Thanks to the rapid advancement of biotechnologies, scientists are now able to scan entirely the human genome, producing high-quality ultradense genotypes and fast localization of genomic deletions and duplications. However, their applications in PD field are still not numerous, and only a few studies have investigated the overall contribution of global CNVs on PD etiology (Pankratz et al 2011; Simon-Sanchez et al 2008; Liu et al 2013; Pamphlett et al 2012; Bademci et al 2010). …”
Section: High-throughput Whole-genome Studies To Map Cnvs In Pdmentioning
confidence: 99%
“…The genome-wide association study found a deletion in tyrosine hydroxylase, enzyme involved in dopamine synthesis, in one adult PD [214] whereas missense mutations in tyrosine hydroxylase gene were already involved in infantile parkinsonism [215].…”
Section: Tyrosine Hydroxylasementioning
confidence: 99%